ASSESSMENT OF VOLTAGE AND CURRENT IMBALANCE ON PURSE SEINE FISHING VESSELS OPERATING IN THE NATUNA SEA: A COMPARATIVE STUDY BASED ON IEEE STD 45-2002 - Demeianto, Bobby; Siahaan, Juniawan Preston; Abrori, M. Zaki L; Tumpu, Mula; Fadiga, Aqshal Ilham; Mahendra, Taufan; Nasution, Akhyar; Pane, Mhd Riswan (Aurelia Journal, 2025)
Although numerous studies have been conducted on voltage and current imbalance in electrical systems, research specifically focusing on these conditions in fishing vessels, particularly those operating in the Natuna Sea, remains very limited. This study aims to analyze the voltage and current imbalance on the generators of purse seine fishing vessels operating in the Natuna Sea, based on the IEEE Std 45-2002 and BKI Volume IV Year 2022 standards. A quantitative approach was employed, involving direct measurements of voltage (both line-to-line and phase-to-neutral) and current at the main distribution panels of five fishing vessels. The reference standard for Line Voltage Unbalance Tolerance (%LVUT) according to IEEE Std 45-2002 is ≤ 3%, while the acceptable limit for current imbalance according to BKI Volume IV Year 2022 is ≤ 15%. The results showed that the average voltage imbalance across the five vessels was below the IEEE tolerance limit (≤ 3%), with the highest recorded value being 4.34% on KM. Palembang Indah II. Meanwhile, current imbalance generally complied with the BKI limit (≤ 15%), except for KM. Rezeki Bersama, which exhibited the highest current imbalance at 30.48%. These findings highlight the need for mitigation measures, such as load redistribution and phase balancing, particularly on vessels with significant imbalance levels. This study provides practical contributions to improving the reliability of vessel electrical systems and enhancing operational safety within Indonesia’s marine fisheries sector.